Síntese de 1,3-oxazinas e 1,2,3-triazóis derivados de cumarina - Dilelio, Marina Cardoso (2019)
In this work we developed a methodology for the synthesis of 1,3-oxazines derived from aminocoumarins by the hydroxymethylation/acetalization reaction with aldehydes catalyzed by H2SO4 in aqueous media. The scope and limitations of this methodology were also studied, presenting good results for different substrates. Twelve compounds were obtained with 34 to 90% yields. Subsequently, N-propargylation of one of the 1,3-oxazines was performed, and then the 1,3-dipolar cycloaddition was carried out with different organic azides, obtaining five 1,4-dissubstituted 1,2,3-triazoles, with 65 to 96% yields. Some selected coumpounds presented antifungal activity against Candida krusei, Candida dublieneses, Candida glabrata and Candida tropicalis. The photophysical properties of the compounds were analyzed, presenting high quantum yields of fluorescence (up to Φf = 0.69) and large Stokes shifts (up to 201 nm).